A Study of the Poverty Alleviation Program for Young Families in Bantarkawung Subdistrict, Brebes - Qolbiyani, Syifa Latif; Kartono, Drajat Tri; Sugiharjo, Sugihardjo; Fitriyani, Norma Latif; Syafrudin, Muhammad (Prosperity: Journal of Society and Empowerment, 2025)
Pahlawan Ekonomi Nusantara (PENA) Muda is a community empowerment program aimed at assisting young families in becoming independent and reducing their reliance on social assistance. Given the importance of implementation effectiveness and the disparities between urban and rural areas, this study focuses on evaluating the effectiveness of the program in rural settings. Using a descriptive qualitative approach, data were collected through interviews, observations, documentation, and the Context, Input, Process, Product (CIPP) evaluation model. The results indicate that the overall effectiveness rate of the program reached 75%, classifying it as effective. Process-related aspects showed average scores of 3.1 for socialization, 3.3 for coaching, 3.2 for mentoring, and 3.5 for monitoring. These findings suggest that although the program is generally effective, some components still have room for improvement, particularly in strengthening socialization and mentoring efforts. The study highlights the significance of context-sensitive implementation and continuous evaluation to enhance the success of community-based programs. In conclusion, the research contributes to the ongoing development of the PENA Muda program and provides insights for optimizing its future implementation, especially in rural areas where tailored approaches are critical for sustainable impact.